2020
DOI: 10.1021/jacs.0c10458
|View full text |Cite
|
Sign up to set email alerts
|

Metal/Ligand Proton Tautomerism Facilitates Dinuclear H2Reductive Elimination

Abstract: Using the doubly protic bis-pyrazole-pyridine ligand (N­(NNH)2), we have synthesized an octahedral IrIII–H [HIr­(κ3-N­(NNH)­(NN–))­(CO)­( t BuPy)]+ ([1-MH]+) from an IrI starting material. This hydride was generated by adding sufficient electron density to the metal center such that it became the thermodynamically preferred site of protonation. It was observed via UV–vis spectroscopy that [1-MH]+ establishes a [ t BuPy] dependent equilibrium with a ligand protonated square-planar IrI [Ir­(N­(NNH)2)­(CO)]+ ([2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 72 publications
(106 reference statements)
1
17
1
Order By: Relevance
“…53 Furthermore, in related studies of MLPT, Rauchfuss, Bullock, and our group have previously demonstrated that the MLPT equilibrium can be perturbed towards the ligand-protonated side by addition of an exogenous hydrogen bonding acceptor such as BF 4 − or CF 3 SO 3 − that can engage in favorable hydrogen bonding interactions with the acidic proton on the ligand backbone. 9,17,18 A similar hydrogen bonding stabilization of the imidazolyl protons is proposed here that disrupts the MLPT equilibrium of [ LH Ir–Cl] with [H– L Ir–Cl] ( Scheme 1, C ) upon addition of excess Cl anions, precluding the formation of latter.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…53 Furthermore, in related studies of MLPT, Rauchfuss, Bullock, and our group have previously demonstrated that the MLPT equilibrium can be perturbed towards the ligand-protonated side by addition of an exogenous hydrogen bonding acceptor such as BF 4 − or CF 3 SO 3 − that can engage in favorable hydrogen bonding interactions with the acidic proton on the ligand backbone. 9,17,18 A similar hydrogen bonding stabilization of the imidazolyl protons is proposed here that disrupts the MLPT equilibrium of [ LH Ir–Cl] with [H– L Ir–Cl] ( Scheme 1, C ) upon addition of excess Cl anions, precluding the formation of latter.…”
Section: Resultssupporting
confidence: 54%
“…To consider how [H-L Ir-Cl] might originate from [ LH Ir][Cl] in solution, one can either propose that proton-transfer from the imidazole to the Ir occurs rst and is followed by Cl À coordination, or that Cl À coordination is followed by ligand to metal proton-transfer. Based on literature precedent wherein addition of electron density to the metal center (thereby increasing its basicity) has been shown to trigger proton-transfer from the ligand to the metal, 9 it is expected that proton-transfer from the…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations